Growth and flowering of carnation cultivated in different pot colors and protected environments - Nagel, Suzielly S.A.; Costa, Edilson; Nagel, Pedro L.; da Silva, Abimael GOMES [UNESP]; Binotti, Flávio F.S.; Vendruscolo, Eduardo P.; Vieira, Gustavo H.C.; Dantas, Thaise (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2024)
The Dianthus caryophyllus L. occupies the second position of the best sold cut flowers after rose. The choice of the environment and the cultivation container is crucial for flower production because, besides permitting higher temperature, light, and relative humidity management, it also impacts yield. This study evaluated the cultivation of yellow carnation in different protected environments and pot colours. The experiment was conducted in a factorial 2 × 4 (greenhouse and nursery x blue, red, brown, and black pots; the black pot was considered the control treatment). The photosynthetically active radiation, substrate temperature, and meteorological variables in the environments were monitored during the experiment’s conduction as well the growth and productivity variables. The greenhouse significantly reduced solar radiation, generating favourable conditions for the initial growth of carnation plants. The nursery maintained higher levels of solar radiation, stimulating its flowering. The cultivation in brown pots provided higher quality plants regarding both vegetative growth and flowering. Therefore, brown pots are an option to substitute the black pots traditionally used for flower production. The use of the blue pot negatively influenced the development of carnation plants.
Keywords: Dianthus caryophyllus; light spectre; luminosity; ornamental species; protected environment